Catalyzed Mizoroki-Heck Reaction or C-H activation - Berteina-Raboin, Sabine (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In the last few decades, research on the elaboration by palladium-catalytic processes of C-C bonds or the activation of C-H bonds has increased considerably. Yet there is still room for much improvement in terms of selectivity, or enantioselectivity, via the development of new ligands or the study of the catalytic effect of other metals to carry out the same chemical transformations. In addition, the attention paid to environmentally friendly methods in terms of the quantities of catalysts, ligands, and solvents is currently indispensable. The Mizoroki-Heck reaction is one of these important catalytic methods which generates C-C bonds in organic synthesis and is also possible by C-H activation. This book, titled "Catalyzed Mizoroki-Heck Reaction or C-H activation" focuses on new advances in the formation of C-C bonds or new C-H activation methods. It contains original research papers and short reviews on the synthesis of biologically active compounds using these catalytic processes, the identification of new catalysts, of new conditions allowing selectivity or enantioselectivity, the activity and stability of catalyst under turnover conditions, and all improvements in catalytic processes.